Stability and Survivability of Alginate Gum-Coated Lactobacillus rhamnosus GG in Simulated Gastrointestinal Conditions and Probiotic Juice Development - Umair Ali; Muhammad Saeed; Zulfiqar Ahmad; Faiz-ul-Hassan Shah; Muhammad Adil Rehman; Tahir Mehmood; Muhammad Waseem; Hammad Hafeez; Muhammad Azam; Afzal Rahman (Journal of Food Quality)
Survivability of probiotics is severely affected by harsh gastrointestinal conditions. In the present study, microbeads of Lactobacillus rhamnosus GG were formulated using alginate (1.5% w/v) and combination of alginate (1.5% w/v) with xanthan gum (0.5% w/v) through an emulsion technique to improve bacterial viability in low pH orange juice and in gastrointestinal conditions. The microbeads were tested for encapsulation efficiency, survivability in bile salt, SGF (simulated gastric juice), SIF (simulated intestinal fluid), and storage stability. Probiotic orange juice was formulated and tested for physicochemical parameters (pH, titratable acidity, and total sugars) and sensorial properties during storage. Gum-coated alginate microbeads (T3) showed higher encapsulation efficiency, i.e., 95.2% compared to alginate microbeads (T2), i.e., 86.85%. Similarly, T3 showed the highest resistance against bile salt (8.50 log CFU/g), SGF (7.95 log CFU/g), and SIF (8.0 log CFU/g) during 80 min exposure compared to T2 and free cells. The viability of gum-coated alginate beads (T3) remained above 107 CFU/g in gastrointestinal conditions and at the end of 21 days storage (8.3 log CFU/mL). All physicochemical parameters of probiotic juice were significantly (p≤0.05) decreased with respect to storage except acidity. In addition, minimal changes in physicochemical parameters were observed in T3 compared to other treatments. Treatment had no significant impact on the sensory characteristics of juice, but storage had a significant effect (p≤0.05) on the sensory characteristics of juice. The alginate gum microbeads improve the survivability of probiotics for targeted delivery. Hence, encapsulated probiotics can be used for functional beverage development to take advantage of their therapeutic benefits.